Corrigendum: What Makes a Difference for Disadvantaged Girls? Investigating the Interplay between Group Composition and Positive Youth Development in Sport - Schaillée, Hebe (Social Inclusion, 2017)
This is a corrigendum to the article "What makes a difference for disadvantaged girls? Investigating the interplay between group composition and positive youth development in sport", authored by Hebe Schaillée, Marc Theeboom and Jelle Van Cauwenberg, and published in Social Inclusion , 3 (3).